PENGARUH MOTIVASI EKSTRINSIK TERHADAP KINERJA PEGAWAI PADA PUSKESMAS TEBING BULANG KECAMATAN SUNGAI KERUH KABUPATEN MUSI BANYUASIN - Muhlisin Muhlisin (Jurnal Media Ekonomi (JURMEK), 2016)
This study aims to determine how the influence of extrinsic motivation on employee performance at the Tebing Bulang Health Center in Sungai Keruh Subdistrict. This study was conducted at the Tebing Bulang Health Center in Keruh River Subdistrict, Musi Banyuasin Regency. This study used primary and secondary data. using statistical equations in processing and discussing data obtained from respondents through a questionnaire media. The results of this study indicate that there is a significant (significant) effect and has a Positive Slope Model (+) this means that if the independent variable namely extrinsic motivation variable (X) increases, then the employee performance dependent variable (Y) will also increase.